Qing-Southeast Asian Interactions in the Context of Border Control and Sovereignty, 1700s–1800s - Boyi Boyi Chen (陳博翼) Chen (Journal of Chinese Humanities, 2022)
This paper discusses Qing China’s interaction with Southeast Asia in the context of border enforcement, that is, the control of movement, and expression of sovereignty. It employs both the imperial logic and the commoners’ daily logic to consider how these three topics interacted with each other in the eighteenth century. I argue that the Qing court considered these issues not in terms of population, territory, or maritime prohibition, but from a standpoint of security and stability, around which the border concerns, ways of controlling people, and sovereignty were all organized. For commoners, simply making a living was the primary concern and the court’s overseas activities had little to do with identity, or an anachronistic concept of sovereignty. The Qing court forbade journeys to Luzon and Batavia, the “barbarian countries” dominated by Spanish and Dutch colonial powers, but intentionally left the door open for commoners to travel to Vietnam. However, when those Chinese people stirred up trouble in Vietnam and returned to the maritime border of China, the Qing government quickly intervened. It had its own logic for enforcing domestic sovereignty and controlling the migration of people between countries.